Hop Extracts and Hop Substances in Treatment of Menopausal Complaints - Keiler, Annekathrin M.; Zierau, Oliver; Kretzschmar, Georg (Planta Medica, 2013)
Hop extract is a long used medicinal product and, regarding hormonal activities, in 1999 a number of prenylflavanones have been identified as its major constituents with 8-prenylnaringenin (8-PN) being the main active estrogenic compound. There have been several in vivo studies performed that demonstrate the potential of hop extract and the single compound 8-PN to alleviate climacteric symptoms like osteoporosis, vasomotoric complaints, and sexual motivation. On the other hand, only a few clinical studies have been performed so far, and these mainly focused on menopausal discomforts, especially hot flushes, yielding rather inconclusive results. Despite preferentially activating estrogen receptor α, 8-PN is only slightly uterotrophic, but it also elucidates estrogenic effects on the mammary gland. In conclusion, although hop extract and especially 8-PN are promising candidates as a relief for climacteric symptoms, data on the safety and efficacy is still scarce.
Keywords: Humulus lupulus L.; Cannabaceae; menopause; 8-prenylnaringenin; xanthohumol; isoxanthohumol; safety